Company financial performance improvement through financial literacy and intellectual capital perspective - Mollah, Moch. Kalam; Suhartini, Suhartini; Basuki H M, Gatot; Nasrudin Khamimi, Fatkhu; Dwi Wahyu Prabowo, Bangkit (Journal of Applied Sciences, Management and Engineering Technology, 2021)
CV. Sarindofood is one of the companies engaged in manufacturing snacks, one of which is a type of Tost and Stick products made from raw materials for industrial corn. CV. Sarindofood uses considerable capital resources, so it needs analysis, especially in the financial sector. This study aims to determine the effect of intellectual capital on corporate financial performance, financial literacy as an understanding of finance. The independent variables used in this study are human capital, structural capital, value-added capital employed, intellectual capital (VAIC). In contrast, the dependent variables include the performance of ROA, ROI, and ROE. The data in this study are the company's financial statement data CV. Sarindofood consists of a balance sheet report and cash flow for five years from 2019 to 2018. The method used in this study uses Multiple Linear Regression, VAIC, and partial t-test, and a simultaneous F-test is used as analysis tools to see each variable's effect. The results of this study indicate that Capital Employee partially has a significant impact on financial performance. Human capital partly has a significant and positive impact on financial performance. Structural capital partially has a significant and positive effect on financial performance. Whereas the value of the results simultaneously shows that the influence of Intellectual Capital on ROA has a significant effect of 60%, Intellectual Capital on RO1 has a significant effect of 69%, and Intellectual Capital on ROE has a significant effect of 55%.